Esterification of levulinic acid into hexyl levulinate over dodecatungstophosphoric acid anchored to Al-MCM-41. Issue 17 (21st November 2016) - Wu, Min; Zhao, Qing-Qing; Li, Jie; Wu, Hai-Yan; Zheng, Xiu-Cheng; Guan, Xin-Xin; Liu, Pu
ABSTRACT: Aluminum-substituted MCM-41 (Al-MCM-41) were hydrothermally synthesised and used as supports to fabricate the mesostructured H3 PW12 O40 (HPW) solid acid catalysts via an impregnation method. The influences of various HPW loadings on the structures of the catalysts were verified by X-ray diffraction (XRD), nitrogen physisorption, scanning electron microscopy (SEM), transmission electron microscopy (TEM), ultraviolet–visible (UV–Vis) spectroscopy and Fourier-transform infrared spectroscopy (FT-IR) measurements and their acidities were evaluated by infrared of pyridine adsorption (Py-IR) and temperature-programmed desorption of ammonia (NH3 -TPD) measurements. The optimisation of the reaction conditions for levulinic acid esterification with n -hexanol such as the reaction temperature and time, the reactant molar ratio, and the catalyst dosages was performed to maximise the conversion of levulinic acid. The effects of various HPW loadings on the conversion of levulinic acid were investigated under the optimised and harsh reaction conditions. The reusability of the catalysts was also investigated. The results showed that these catalysts retained the hexagonal mesoporous structure of Al-MCM-41 and the Keggin characteristic of HPW, although their textural parameters decreased with increasing loading of HPW. In particular, the catalysts were found to be efficient in the esterification of levulinic acid with n -hexanol, resulting in hexyl levulinate which could replace the petroleum-derived chemical feedstocks.